Spare me the details: How the type of information about automated interviews influences applicant reactions - Markus Langer; Kevin Baum; Cornelius J. König; Viviane Hähne; Daniel Oster; Timo Speith (International Journal of Selection and Assessment, 2021)
Applicants seem to react negatively to artificial intelligence-based automated systems in personnel selection. This study investigates the impact of different pieces of information to alleviate applicant reactions in an automated interview setting. In a 2 (no process information vs. process information)~~2 (no process justification vs. process justification) between-subjects design, participants (N~=~124) received respective information and watched a video showing an automated interview. Testing mediation effects via different applicant reaction variables indicated that process justification is better than process information which can even impair applicant reactions. However, information did not increase organizational attractiveness compared to not receiving any information. This study sheds light on what type of information contributes to positive and negative applicant reactions to automated systems.
Keywords: 650; algorithms; applicant reactions; explainable artificial intelligence; human-computer-interaction; information; personnel selection